HUMANIZING BRANDS IN THE DIGITAL ERA: THE ROLES OF BRAND PERSONALITY AND EMPATHIC COMMUNICATION IN SHAPING CUSTOMER LOYALTY THROUGH EMOTIONAL CONNECTION - Zulfia K. Abdussamad; Andi Faisal; Salim Basalamah (Accounting Profession Journal (APAJI), 2026)
This study examines how humanized branding influences customer loyalty in the digital era by investigating the roles of brand personality, empathic communication, and emotional connection. Grounded in Relationship Marketing, the research analyzes whether emotional connection functions as a key relational mechanism linking brand humanization to loyalty outcomes. A quantitative explanatory design was employed using survey data collected from 195 Indonesian digital consumers who had interacted with brands through online platforms and made at least one online purchase within the previous six months. The data were analyzed using SmartPLS and the PLS-SEM approach. The findings reveal that brand personality has a positive and significant effect on emotional connection, but does not directly influence customer loyalty. In contrast, empathic communication positively affects both emotional connection and customer loyalty. Emotional connection itself exerts a strong positive influence on customer loyalty. Mediation analysis further demonstrates that emotional connection fully mediates the relationship between brand personality and customer loyalty, while partially mediating the effect of empathic communication on customer loyalty. These findings suggest that in digital markets, symbolic brand distinctiveness alone is insufficient to secure loyalty unless it generates meaningful affective attachment. The study contributes to contemporary branding literature by demonstrating that emotional connection serves as the principal mechanism through which brand humanization translates into loyalty. For practitioners, the findings underscore the importance of combining distinctive brand identity with emotionally responsive communication to strengthen long-term customer relationships.